Reinventing global democracy - Scholte, Jan Aart (European journal of international relations, 2014)
How can democracy be suitably formulated in face of the more global character of contemporary society? Modern ideas and practices of ‘people’s rule’ (whether in a statist or a cosmopolitan mode) fall short as frameworks for global democracy. Statist approaches to global democracy have a host of behavioural, institutional, historical and cultural problems. Modern cosmopolitan approaches do better in addressing contemporary social changes, but are deficient in terms of their globalist tendencies, often oversimplified notions of political identity, limited cultural reflexivity, usually tame responses to resource inequalities and anthropocentrism. To address these shortcomings one might explore an alternative of ‘postmodern global democracies’ built around principles of transscalarity, plural solidarities, transculturality, egalitarian distribution and more ecologically framed ideas of political rights and duties.